The relationship between altruism and equal sharing. Evidence from inter vivos transfer behavior - Elin Halvorsen; Thor O. Thoresen (Statistics Norway, Research Department, 2005)
Several studies reject the implications of the altruism model. In this study it is argued that parents who transfer resources to their children both are altruistic and influenced by an equal division fairness norm. Under such motives, the degree of income compensation should be stronger in one-child families and we expect the altruism motive to dominate the fairness norm when income differences between siblings are large. The results suggest that equal divisions are intentional and weighted against altruistic motives.
Keywords: D19; D64; H21; 330; inter vivos gifts; altruism; equal sharing; compensatory transfer